Qualitative findings from North America's first drug compassion club. - Jeanette Bowles; Eris Nyx; Jeremy Kalicum; Thomas Kerr (PLoS ONE)
In Canada, the ongoing fatal overdose crisis remains driven by the unpredictable potency and content of the illicit drug supply. From August 2022 until October 2023, the Drug User Liberation Front [DULF] operated a drug compassion club [CC], which sells drugs of known composition and purity without medical oversight. The present study is a qualitative evaluation of this project. From December 2022 to February 2023, we interviewed 16 CC members about their experiences with DULF's CC. Using a semi-structured interview guide, participants were interviewed in a private space to ensure confidentiality. Thematic analysis was used to code for a priori and unexpected themes. Participants spoke positively of their experiences with the CC, which ranged from lower overdose risk, health improvements, preference for the drug purchasing process, and mutual respect and trust among CC members, founders, and staff. No participants reported overdosing on CC-sourced drugs, and drugs were described as safe and reliable. For opioid users, the tolerance developed for opioid-potent fentanyl hampered the transition to CC heroin. Suggestions for CC improvements were also identified. Despite political backlash to the project, the CC appears to be a novel and promising approach to reducing overdose morbidity in high needs communities. By promoting participant autonomy, regulating an unstable drug supply, and creating community, this intervention has reduced self-reported overdose risk and improved the health and social wellbeing of members. No overdoses reported from CC-sourced drugs suggests that authorizing, expanding and continually evaluating the CC model is warranted.